Ultra-fast, High-Bandwidth Coherent cw THz Spectrometer for Non-destructive Testing - Liebermeister, Lars; Nellen, Simon; Kohlhaas, Robert; Breuer, Steffen; Schell, Martin; Globisch, Björn (Journal of infrared, millimeter and terahertz waves, 2019)
Continuous wave THz (cw THz) systems define the state-of-the-art in terms of spectral resolution in THz spectroscopy. Hitherto, acquisition of broadband spectra in a cw THz system was always connected with slow operation. Therefore, high update rate applications like inline process monitoring and non-destructive testing are served by time domain spectroscopy (TDS) systems. However, no fundamental restriction prevents cw THz technology from achieving faster update rates and be competitive in this field. In this paper, we present a fully fiber-coupled cw THz spectrometer. Its sweep speed is two orders of magnitude higher compared to commercial state-of-the-art systems and reaches a record performance of 24 spectra per second with a bandwidth of more than 2 THz. In the single-shot mode, the same system reaches a peak dynamic range of 67 dB and exceeds a value of 100 dB with averaging of 7 min, which is among the highest values ever reported. The frequency steps can be as low as 40 MHz. Due to the fully homodyne detection, each spectrum contains full amplitude and phase information. This demonstration of THz-spectroscopy at video-rate is an essential step towards applying cw THz systems in non-destructive, in line testing.